Molecular epidemiology and resistance modulation of Streptococcus spp. in subclinical goat mastitis in Pakistan - Ashraf Ali; Muhammad Ijaz; Arslan Ahmed; Muhammad Umar Javed; Hamza Rasheed; Maria Batool; Kehkshan Shahid; Gulbaz Anwar; Mahpara Safdar (Small Ruminant Research, 2026)

Molecular insights, resistance profiling, and in silico structural modeling of extended-spectrum beta-lactamase-producing E. coli in camels - Mahpara Safdar; Muhammad Ijaz; Arslan Ahmed; Muhammad Umar Javed; Kehkshan Shahid; Maria Batool; Gulbaz Anwar; Hamza Rasheed; Ashraf Ali (Veterinary Research Communications, 2026)

Global perspectives on the curricular integration of nature-based solutions in hydrology and water resources management education - Mark Bryan Alivio; Kristina Potočki; Pavel Raška; Peter Ameh Adegede; Tanveer Mehedi Adyel; Hafzullah Aksoy; Mary Bourke; Yonca Cavus; Mariana Madruga de Brito; Moctar Dembélé; Ashraf M. Elmoustafa; Kristian Förster; et al. (Journal of Cleaner Production, 2026)

Kinetics of volatile release from packaging intended for fresh cut produce: An investigation based on headspace-SPME-GC-MS - Jahan Zaib Ashraf; Sandra Pati; Flora Macolino; Ilario Losito; Maria Luisa Amodio; Giancarlo Colelli (Food Packaging and Shelf Life, 2026)

Sustainable Laccase Production by Anoxybacteroides rupiense UE27 Using Desmostachya bipinnata Biomass: Optimisation and Application in Textile Effluent Treatment - Haniah Saeed; Bushra Rehman; Uroosa Ejaz; Maria Muhammad Ashraf; Amal Siraj; Areesha Mustafa; Muhammad Sohail (Environmental Microbiology, 2026)
Laccase has been widely reported for the detoxification of industrial effluents, yet large‐scale applications require cost‐effective production. This study utilised an innovative approach by employing biomass from the halophyte Desmostachya bipinnata, which has not been previously reported for microbial enzyme production. A newly discovered bacterial species, Anoxybacteroides rupiense, was used for laccase production. Initially, the factors impacting laccase production by the thermophilic strain of A. rupiense UE27 (Genome Project JBHLFH010000000.1) were screened for their significant effects using the Plackett–Burman design. Consequently, Response Surface methodology was adopted to optimise the significant factors, resulting in a maximum laccase yield of 51.69 U L −1 at pH 6.39 and in presence of 0.59 mM CuSO 4 , representing a 4.29‐fold increase compared to the unoptimised conditions. AFM revealed comminution in the plant biomass and FTIR analysis confirmed laccase‐mediated lignin degradation in D. bipinnata biomass, evidenced by shifts in aromatic CC (1597–1650 cm −1 ), CH methyl (2850–2918 cm −1 ) and phenolic OH (3300–3400 cm −1 ) regions. Moreover, growth of A. rupiense UE27 in the presence of textile effluent resulted in 70.6% decolourisation with the subsequent laccase production. Hence, this study presents a sustainable and innovative approach for developing wild biomass‐based processes for the cost‐effective production of laccase by thermophilic bacteria.

Comparative insights into molecular characterization and resistance profiling of methicillin-resistant Staphylococcus aureus across dairy livestock in Pakistan - Muhammad Ijaz; Maria Batool; Muhammad Umar Javed; Hamza Rasheed; Arslan Ahmed; Ali Abdullah Jabir; Kehkshan Shahid; Ashraf Ali; Muhammad Talha (Veterinary Research Communications, 2026)

Comprehensive study on the migration on non-intentionally added substances from food contact films of PBS, PLA, and their blends - Jahan Zaib Ashraf; Emmanouil D. Tsochatzis; Sandra Pati; Maria Luisa Amodio; Annalisa Apicella; Loredana Incarnato; Mario M. Martinez; Ivan M. Lopez-Rodulfo; Giancarlo Colelli (Food Packaging and Shelf Life, 2026)

Photoperiod and temperature: Key abiotic drivers of horticultural crop physiology in a changing climate - Muhammad Atiq Ashraf; Shumaila Nawaz; Uzma Bilal; Maria Abubakar; Shumaila Anam; Muhammad Azam; Burhan Khalid; Abdullah; Muhammad Asim; Rabbya Rayan Shah; Muhammad Ateeq (Biologia, 2026)

A novel hybrid MOF–metal oxide electrochemical sensor for ultra-trace detection of cadmium ions - Sabah Haider; Mujahid Mustaqeem; Maria Zaib; Mohammed Ashraf Gondal; Umar Farooq; Muhammad Salman; Rabia Akram Bajwa (Journal of Environmental Chemical Engineering, 2025)

Exploring evolutionary perspectives and antibiogram analysis of biofilm-forming Staphylococcus aureus in goat mastitis - Muhammad Umar Javed; Muhammad Ijaz; Arslan Ahmed; Hamza Rasheed; Ali Abdullah Jabir; Maria Batool; Kehkshan Shahid; Ashraf Ali; Muhammad Talha (Veterinary Research Communications, 2025)

An integrated participatory framework for WEFE nexus strategic planning: The Jordan Valley case study - Nikolaos P. Nikolaidis; Katerina Troullaki; Maria A. Lilli; Suleiman Halasah; David Lehrer; Stelios Rozakis; Shlomo Wald; Ashraf Al Ajrami; Shaddad Al-Attili; Shiri Zemah-Shamir; Anan Jayyousi; Iddo Kan; et al. (Journal of Environmental Management, 2025)

CRISPR-Cas9 mediated understanding of plants’ abiotic stress-responsive genes to combat changing climatic patterns - Muhammad Waqas Choudry; Rabia Riaz; Pashma Nawaz; Maria Ashraf; Bushra Ijaz; Allah Bakhsh (Functional & Integrative Genomics, 2024)

Revealing mechanisms regulating diurnal groundwater level fluctuation in a temperate fen peatland: A spatiotemporal exploration - Omar Ashraf Nimr; Niels Van Putte; Patrick Meire; Mateusz Grygoruk; Goedele Verreydt; Maria Grodzka-Łukaszewska (Journal of Hydrology, 2024)

Fiber and nanofiber based edible packaging for enhancing the shelf life of food: A review - Manisha Joshi; Krishna Aayush; Kanika Sharma; Ipsheta Bose; Asma Ashraf Khan; Maria Atanassova; Tianxi Yang; Otilia Cristina Murariu; Somesh Sharma; Gianluca Caruso (Food Bioscience, 2024)

Geochemical Investigation of OCPs in the Rivers Along with Drains and Groundwater Sources of Eastern Punjab, Pakistan - Asmat Ali; Zahid Ullah; Maria Siddique; Junaid Ghani; Abdur Rashid; Warda Khalid; Muhammad Inayat Ullah Khan; Waqas Ashraf (Exposure and Health, 2024)

Exploring homologous recombination repair and base excision repair pathway genes for possible diagnostic markers in hematologic malignancies - Sumaira Fida Abbasi; Ishrat Mahjabeen; Neelam Parveen; Imama Qamar; Maria Fazal Ul Haq; Rabia Shafique; Nadia Saeed; Nida Sarosh Ashraf; Mahmood Akhtar Kayani (Molecular Genetics and Genomics, 2023)

Narcissus pseudonarcissus L. (Amaryllidaceae) bulb metabolite profiling and biological activities - Youstina Refaat Boshra; Eman Zekry Attia; Ahmed G. Darwish; Maria Refaat Boshra; Mohamed N. Amin; Ashraf Nageeb Elsayed Hamed; Samar Yehia Desoukey; John Refaat Fahim (South African Journal of Botany, 2023)

Mycotoxins in Zea mays , their quantification and HPLC analysis of physico-biological detoxification - Maria Murad; Khuram Shahzad Ahmad; Shazia Iram; Nafeesa Qudsia Hanif; Mahwash Mahar Gul; Ashraf Y. Elnaggar; Zeinhom M. El-Bahy (Natural Product Research, 2022)

Salicylic Acid– and Ascorbic Acid–Induced Salt Tolerance in Mung bean (Vigna radiata (L.) Wilczek) Accompanied by Oxidative Defense Mechanisms - Maria Nawaz; Muhammad Yasin Ashraf; Ameer Khan; Fahim Nawaz (Journal of Soil Science and Plant Nutrition, 2021)

Citalopram Reduces Aggregation of ATXN3 in a YAC Transgenic Mouse Model of Machado-Joseph Disease - Naila S. Ashraf; Sara Duarte-Silva; Emily D. Shaw; Patrícia Maciel; Henry L. Paulson; Andreia Teixeira-Castro; Maria do Carmo Costa (Molecular Neurobiology, 2019)

Synthesis and enzyme inhibitory kinetics of some novel 3-(substituted benzoyl)-2-thioxoimidazolidin-4-one derivatives as α-glucosidase/α-amylase inhibitors - Rabia Qamar; Aamer Saeed; Maria Saeed; Babar Hussain Shah; Zaman Ashraf; Qamar Abbas; Sung Yum Seo (Medicinal Chemistry Research, 2018)

GDF11 Treatment Attenuates the Recovery of Skeletal Muscle Function After Injury in Older Rats - Yu Zhou; Neel Sharma; David Dukes; Maria B. Myzithras; Priyanka Gupta; Ashraf Khalil; Julius Kahn; Jennifer S. Ahlberg; David B. Hayes; Michael Franti; Tracy Criswell (The AAPS Journal, 2017)